2014
DOI: 10.1111/bjh.13065
|View full text |Cite
|
Sign up to set email alerts
|

Targeting PI3‐kinase (PI3K), AKT and mTOR axis in lymphoma

Abstract: Targeted therapy represents a transformation in oncology, a field that has relied primarily on non-selective cytotoxic therapies. Phosphatidylinositol 3-kinase (PI3K) is a family of ubiquitous signalling molecules involved in a wide variety of cellular processes and likewise, in a broad selection of human cancers. The discovery that the p110-δ form of PI3K is differentially expressed in normal and malignant lymphocytes has led to the development of specific inhibitors that are currently in clinical trials for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
68
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(69 citation statements)
references
References 96 publications
1
68
0
Order By: Relevance
“…Furthermore, PI3K, a common intracellular downstream effector of glucose and insulin, was shown to be associated with CFTR activation (Blachly and Baiocchi 2014). Blachly and Baiocchi (2014) showed that PI3K is involved in the modulation of CFTR by insulin in kidney cells, highlighting a possible association between the lack of insulin in the STZ‐induced diabetic animal model and CFTR dysfunction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, PI3K, a common intracellular downstream effector of glucose and insulin, was shown to be associated with CFTR activation (Blachly and Baiocchi 2014). Blachly and Baiocchi (2014) showed that PI3K is involved in the modulation of CFTR by insulin in kidney cells, highlighting a possible association between the lack of insulin in the STZ‐induced diabetic animal model and CFTR dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Blachly and Baiocchi (2014) showed that PI3K is involved in the modulation of CFTR by insulin in kidney cells, highlighting a possible association between the lack of insulin in the STZ‐induced diabetic animal model and CFTR dysfunction. Nevertheless, more studies on the complex relationship between the endocytic machinery components and diabetes features, such as hyperglycemia, lack of insulin, and albumin overload, are indeed necessary (Blachly and Baiocchi 2014). …”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] The observation that mTOR is aberrantly activated in a variety of malignancies has generated intense interest in this kinase as a target for antineoplastic therapy, particularly for lymphoid malignancies. 1,3,[5][6][7][8][9][10][11] Over the last decade, rapamycin-based mTOR inhibitors have proven effective in certain lymphomas. 7,9,10 However, their efficacy is limited by incomplete inhibition of mTOR complex 1 (mTORC1) and by activation of AKT and downstream prosurvival pathways through a variety of feedback mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…1,3,[5][6][7][8][9][10][11] Over the last decade, rapamycin-based mTOR inhibitors have proven effective in certain lymphomas. 7,9,10 However, their efficacy is limited by incomplete inhibition of mTOR complex 1 (mTORC1) and by activation of AKT and downstream prosurvival pathways through a variety of feedback mechanisms. 6,[11][12][13][14][15] To overcome this limitation, inhibitors targeting the kinase activities of both mTORC1 and mTORC2 have been developed.…”
Section: Introductionmentioning
confidence: 99%
“…Over-active Akt1 is a hallmark of diverse human malignancies [3,4] and linked to reduced survival outcomes [5,6]. Indeed, Akt1 is as a leading drug target in cancer [7,8]. Over 300 clinical trials are completed or underway that involve targeting the Akt1 signaling pathway.…”
Section: Introductionmentioning
confidence: 99%